Operative simulation of anterior clinoidectomy using a rapid prototyping model molded by a three-dimensional printer - Okonogi, Shinichi; Kondo, Kosuke; Harada, Naoyuki; Masuda, Hiroyuki; Nemoto, Masaaki; Sugo, Nobuo (Acta neurochirurgica, 2017)
Background As the anatomical three-dimensional (3D) positional relationship around the anterior clinoid process (ACP) is complex, experience of many surgeries is necessary to understand anterior clinoidectomy (AC). We prepared a 3D synthetic image from computed tomographic angiography (CTA) and magnetic resonance imaging (MRI) data and a rapid prototyping (RP) model from the imaging data using a 3D printer. The objective of this study was to evaluate anatomical reproduction of the 3D synthetic image and intraosseous region after AC in the RP model. In addition, the usefulness of the RP model for operative simulation was investigated. Methods The subjects were 51 patients who were examined by CTA and MRI before surgery. The size of the ACP, thickness and length of the optic nerve and artery, and intraosseous length after AC were measured in the 3D synthetic image and RP model, and reproducibility in the RP model was evaluated. In addition, 10 neurosurgeons performed AC in the completed RP models to investigate their usefulness for operative simulation. Results The RP model reproduced the region in the vicinity of the ACP in the 3D synthetic image, including the intraosseous region, at a high accuracy. In addition, drilling of the RP model was a useful operative simulation method of AC. Conclusions The RP model of the vicinity of ACP, prepared using a 3D printer, showed favorable anatomical reproducibility, including reproduction of the intraosseous region. In addition, it was concluded that this RP model is useful as a surgical education tool for drilling.